2009
DOI: 10.2527/jas.2009-1818
|View full text |Cite
|
Sign up to set email alerts
|

Effects of duration of zilpaterol hydrochloride and days on the finishing diet on carcass cutability, composition, tenderness, and skeletal muscle gene expression in feedlot steers1

Abstract: Preselected carcasses (n = 112) from feedlot steers fed zilpaterol hydrochloride (ZH; 8.33 mg/kg, DM basis) in a serial slaughter experiment were evaluated to determine the effects of ZH upon carcass cutability, composition, and tenderness. A 4 x 4 factorial arrangement of treatments in a completely random design was used with days on ZH (0, 20, 30, and 40 d before slaughter with a 3-d withdrawal) and days on the finishing diet (DOF; 136, 157, 177, and 198 d). No relevant ZH duration x slaughter group interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
46
3
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 38 publications
7
46
3
2
Order By: Relevance
“…Carcasses from ZH heifers had 35% less BF, but there was no effect on marbling score. The reduction in BF was much greater than the 5% reduction reported by Rathmann et al (2009), but these authors also found no effect on marbling. In contrast, Montgomery et al (2009) reported that BF thickness was unaffected by ZH, but marbling score was reduced instead.…”
Section: Growth-promoting Technologies Effectscontrasting
confidence: 47%
See 1 more Smart Citation
“…Carcasses from ZH heifers had 35% less BF, but there was no effect on marbling score. The reduction in BF was much greater than the 5% reduction reported by Rathmann et al (2009), but these authors also found no effect on marbling. In contrast, Montgomery et al (2009) reported that BF thickness was unaffected by ZH, but marbling score was reduced instead.…”
Section: Growth-promoting Technologies Effectscontrasting
confidence: 47%
“…Kellermeier et al (2009) conducted a similar study in steers and reported that average muscle fiber diameter increased by 3% and 6% when anabolic implants and ZH were utilized, respectively. While Rathmann et al (2009) and Baxa et al (2010) did not directly measure fiber CSA or diameter, they did indicate increases in the mRNA expression of type IIX muscle fibers demonstrated ZH increased protein synthesis of this isoform. Other B-AA have also increased muscle fiber CSA.…”
Section: Growth-promoting Technologies Effectsmentioning
confidence: 99%
“…This increase in muscle mass is attributed to an increase in muscle protein synthesis, a reduction in protein degradation or some combination of both (Scramlin et al, 2010). In addition, other β-AA increase the transcriptional activity of calpastatin (Rathmann et al, 2009), which could be the reason for the reduction in tenderness that has been reported in some studies (Leheska et al, 2008;Kellermeier et al, 2009).…”
Section: Introductionmentioning
confidence: 98%
“…It is believed that with the feeding of BAAs the amount of the specific enzymes are changed causing an increase in the enzyme calpastatin, which is an enzyme that decreases enzymatic turnover. Alternatively Rathmann et al (2009) observed no changes in enzymatic activity with ZH fed cattle when compared to control. The author suggested that the difference in WBS from cattle fed ZH may be from an increase in myosin heavy chain proteins which correlates with the observed hypertrophy of muscling.…”
Section: Warner Bratzler Shearmentioning
confidence: 96%
“…Generally, an increase in muscle fiber diameter (hypertrophy) will result in tougher meat. Rathmann et al (2009) reported that an increase in Warner Bratzler Shear force was likely due to the swelling of the muscle fiber (hypertrophy), this was evident because of the increase in myosin heavy chain proteins rather than a change in the protease enzyme activity within the muscle. Along with tenderness, evaluation of color is also a key aspect for determining meat quality.…”
Section: Carcass Effectsmentioning
confidence: 99%